1974
DOI: 10.1083/jcb.61.2.316
|View full text |Cite
|
Sign up to set email alerts
|

CALCIUM PHOSPHATE GRANULES IN THE HEPATOPANCREAS OF THE BLUE CRAB CALLINECTES SAPIDUS

Abstract: The hepatopancreas of the adult male blue crab Callinectes sapidus in intermolt was found to contain substantial amounts of calcium, magnesium, and inorganic phosphorus, averaging about 260, 20, and 250 µg-atoms per g wet tissue, respectively, accounting for over 10% of the tissue dry weight . Electron microscopy of the intact tissue showed three qualitatively different granular structures having electron densities suggestive of high mineral content . After fractionation of the tissue using centrifugal techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(63 citation statements)
references
References 15 publications
1
57
1
4
Order By: Relevance
“…It was previously observed that decapods, which do not develop gastroliths, can store, in other storage sites such as hepatopancreas or haemolymph, not only calcium and carbonate but also phosphate ions used for the mineralization of each new cuticle (Becker et al, 1974;Corrêa, 2002Corrêa, , 2009Sparkes and Greenaway, 1984;Travis, 1955).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously observed that decapods, which do not develop gastroliths, can store, in other storage sites such as hepatopancreas or haemolymph, not only calcium and carbonate but also phosphate ions used for the mineralization of each new cuticle (Becker et al, 1974;Corrêa, 2002Corrêa, , 2009Sparkes and Greenaway, 1984;Travis, 1955).…”
Section: Discussionmentioning
confidence: 99%
“…Once in the gut, the reabsorption of the ions after the granule chemical and enzymatic dissolution may also occur, as suggested by Becker et al (1974). Nott and Nicolaidou (1993), fed a carnivorous gastropod (Nassarius reticulatus) with another gastropod (Littorina littorea) hepatopancreas which contained intracellular phosphate granules.…”
Section: Biomagnification and Trophic Transfermentioning
confidence: 99%
“…In some species, these concretions remain in the cell for a relatively long period of time before they are excreted (Fowler, 1987;Sullivan et al, 1988;Nott, 1991). Actually granules were found in the digestive lumen of the crab Callinectes sapidus (Becker et al, 1974;Guary & Negrel, 1981) and of the copepod Tigriopus brevicornis (Barka, 2007) suggesting that metal detoxification occurs (if the release of granules into the lumen is followed by an excretion in the gut) (Fig. 6).…”
Section: Metal Detoxificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Outro papel é a absorção de nutrientes e outros componentes da dieta (YONGE, 1924;LOIZZI, 1971;LOIZZI & PETERSON, 1971;GIBSON & BARKER, 1979;JOHNSON, 1980). O hepatopâncreas também é responsável pelo armazenamento de cálcio e fosfato do exoesqueleto durante o ciclo da muda (BECKER et al,1974;CHEN et al, 1974;LORET & DEVOS, 1992) e glicogênio e lipídeos durante períodos de abundância de alimentos (YONGE, 1924; VAN WEEL, 1974;GIBSON & BARKER, 1979;JOHNSON, 1980). Pelo menos 4 tipos celulares são reconhecidos nesse órgão e foram classificadas de acordo com JACOBS em (1928): (1) células "E" (embrionárias), que se originam por mitose na região distal do túbulo e se diferenciam quando migram proximalmente; (2) "F" (fibrilares), que possuem um citoplasma granular e um vacúolo supranuclear que se expande conforme a maturação da célula; (3) "R" (absortivas), que contém gotículas de glicogênio e lipídeos; e (4) "B" (blister, vesiculares), que contém um único e grande vacúolo enzimático cercado por um fino citoplasma.…”
Section: I4 Tecidos Que Armazenam E Transportam Cálciounclassified